Diseño y simulación de una maquina dobladora de tubo de 1-½ ´´ para el taller Hierros Gama del Municipio de Palermo. - Gomajoa Cortés, Luis Sebastián (Universidad Antonio Nariño, 2021)
One of the problems, which is presented in the ornamentation workshops in the municipality of Palermo, Huila, is the lack of a tube bending machine to develop and build structures that require bends, mainly of one and a half inch tubes (1 ½ "), widely used and demanded in the development of different products, and thus provide higher quality services to the customer. In the degree project, the design of a one and a half inch (1 ½ ") tube bending machine is presented. The historical-logical method is used for the study of the art, the induction-deduction method for the analysis of the information and the analysis and synthesis method to determine the key factors of the study. The design criteria were defined as the size of the machine (height 630 mm, width 550 mm, length 1200 mm), diameter of the bending die (240 mm), contemplating a bending factor 2.5 and a bending power of 3, 93 Hp. It was verified by means of simulation that the one and a half inch tube can be deformed with a load of 123472.06 N, achieving a maximum slope of 3.4 mm at the end of the tube. The machine design works with a maximum angle of 45° to exert the bend, in two seconds for the first deformation and is complemented by the use of a five-ton hydraulic jack to lift 5 mm to adjust the tube.